Spray and atomization characteristics of gas-centered swirl coaxial injectors. (June 2017) - Anand, Rahul; Ajayalal, PR; Kumar, Vikash; Salih, A; Nandakumar, K
To achieve uniform and efficient combustion in a rocket engine, a fine uniform spray is needed. The same is achieved by designing an injector with good atomization characteristics. Gas-centered swirl coaxial (GCSC) injector elements have been preferred recently in liquid rocket engines because of an inherent capability to dampen the pressure oscillations in the thrust chamber. The gas-centered swirl coaxial injector chosen for this study is proposed to be used in a semi-cryogenic rocket engine operating with oxidizer rich hot exhaust gases from the pre-burner and liquid kerosene as fuel. In this paper, nine different configurations of gas-centered swirl coaxial injector, sorted out by studying the spray angle and coefficient of discharge with swirl number varying from 9 to 20 and recess ratio of 0.5, 1, and 1.5 are investigated for their atomization characteristics. Spray uniformity, spray cone angle, and droplet size in terms of Sauter mean diameter and mass median diameter are studied at various momentum flux ratios for all configurations. Sauter mean diameter is almost independent of recess ratio, whereas cone angle was inversely proportional to the recess ratio. A finer atomization was observed for injectors of high swirl number but the pressure drop also increased to achieve the same flow rate. An injector of medium swirl number and recess ratio of 1.5 is deemed most fit for above-mentioned application.